SINERGI FINTECH DENGAN PERBANKAN SYARIAH DALAM PERSPEKTIF HUKUM - Andi Fariana Ahmad Syafii (istinbath, 2018)
Abstract: The digital era that cannot be stifled by its development has a negative and positive impact on humans in all dimensions of life. However, this important development should be used as an opportunity and challenge to provide benefits and convenience.Similarly in the financial industry, where the development of information technology has penetrated and entered all financial sectors, including the banking industry. Islamic banking that carries Islamic values must also participate and utilize this phenomenon and collaborate with Fintech (Financial Technology) for the purpose of benefit, and this is very possible to be done while upholding the values of sharia. For this reason, regulation is indispensable so that collaboration that is carried out will result in comfort, tranquility and most importantly, emphasizes that compulsory avoidance from transactions that are Ribawi, Gharar, Maysir, Tadlis, Risywah and Israf and transactions on objects that are haram or immoral. OJK as a regulator and supervisor in the financial industry has issued regulations relating to this matter, and supported by the DSN-MUI Fatwa, while it is considered currently as adequate, other legal products are needed to anticipate the development and utilization of IT in the Islamic finance industry, especially Islamic Banking in the future. Abstrak: Era digital yang tidak bisa dibendung perkembangannya memberikan dampak negatif dan positif bagi manusia dalam semua dimensi kehidupannya. Namun, perkembangan yang niscaya adanya ini selayaknya dijadikan peluang dan tantangan untuk memberikan keuntungan dan kemudahan. Demikian pula dalam industri keuangan dimana perkembangan teknologi infomasi merambah dan masuk kesemua sektor keuangan termasuk juga industri perbankan. Perbankan syariah yang mengusung nilai-nilai syariah juga harus ikut dan memanfaatkan fenomena ini serta berkolaborasi dengan fintech (financial technologi) untuk tujuan kemaslahatan, dan hal ini sangat mungkin dilakukan dengan tetap menjunjung tinggi nilai-nilai syariah. Untuk itu regulasi sangat diperlukan agar kolaborasi yang dilakukan melahirkan kenyamanan, ketenangan serta yang paling utama tetap menekankan bahwa wajib terhindar dari transaksi yang ribawi, gharar, maysir, tadlis, risywah dan israf dan transaksi atas obyek yang haram atau maksiat. OJK sebagai regulator dan pengawas dalam industri keuangan telah mengeluarkan Peraturan yang berkaitan dengan hal tersebut, dan didukung dengan Fatwa DSN-MUI maka sementara dirasa cukup memadai namun kedepan diperlukan produk-produk hukum lain untuk mengantisipasi perkembangan dan pemanfaatan IT dalam industri keuangan syariah khususnya Perbankan Syariah.